"The stroke is eighty nine": understanding unprofessional behaviour through physician-authored prose. Issue 1 (1st June 2007) - Rees, C E; Knight, L V
Abstract : The unprofessional behaviour of medics is explored through their depiction in two physician-authored books—the novel Bodies and the autobiography Bedside stories: confessions of a junior doctor . Using the Integrative Model of Behavioural Prediction, not only the range and nature of professionalism lapses outlined in these books but also the reasons behind such unprofessional behaviours are examined. The books contained examples of lapses in professionalism outlined in research investigating the unprofessional behaviour of medical students, such as communication violations, objectification of patients and causing harm to patients. More interestingly, various reasons behind lapses in professionalism were found. Most examples of unprofessional behaviour were unintentional acts and therefore due to environmental constraints and skill deficits. Seemingly intentional acts were largely influenced by normative beliefs—that is, people feeling pressurised to act unprofessionally. Further research is needed to examine the depiction of lapses in professionalism in a wider range of physician-authored prose.